Impact of Social Determinants of Health on the Emerging COVID-19 Pandemic in the United States - Singu, Sravani; Acharya, Arpan; Challagundla, Kishore; Byrareddy, Siddappa N. (Frontiers in Public Health, 2020)
A novel coronavirus (2019-nCoV) caused a global pandemic in the months following the first four cases reported in Wuhan, China, on December 29, 2019. The elderly, immunocompromised, and those with preexisting conditions—such as asthma, cardiovascular disease (CVD), hypertension, chronic kidney disease (CKD), or obesity—experience higher risk of becoming severely ill if infected with the virus. Systemic social inequality and discrepancies in socioeconomic status (SES) contribute to higher incidence of asthma, CVD, hypertension, CKD, and obesity in segments of the general population. Such preexisting conditions bring heightened risk of complications for individuals who contract the coronavirus disease (COVID-19) from the virus (2019-nCoV)—also known as “severe acute respiratory syndrome coronavirus 2” (SARS-CoV-2). In order to help vulnerable groups during times of a health emergency, focus must be placed at the root of the problem. Studying the social determinants of health (SDOH), and how they impact disadvantaged populations during times of crisis, will help governments to better manage health emergencies so that every individual has equal opportunity to staying healthy. This review summarizes the impact of social determinants of health (SDOH) during the COVID-19 pandemic.